Predation and life table parameters of exotic predator Phytoseiulus longipes (Evans) and local Neoseiulus barkeri (Hughes) on tomato in laboratory - Azandeme-Hounmalon, G.Y.; Souna, D.A.; Onzo, A.; Negloh, K.; Akadiri, M.; Nouhoum, A.; Tamo, M.; Martin, T. (2025)
Tetranychus evansi is a key pest of solanaceous crops in Africa on which it causes serious economic damages. Various approaches for its control have been tested, including cultural practices, host-plant resistance, and the use of synthetic and botanical pesticides, all with limited success. Biological control appears, however, as the most promising eco-friendly control strategy worth to be experimented. In these laboratory studies we compared the potentials of two predatory mite species, the one exotic to Benin (Phytoseiulus longipes) and the other endogenous (Neoseiulus barkeri) in controlling T. evansi on tomato. Thereby, predation, oviposition and survivorship of adult females P. longipes and N. barkeri as well as their biological and demographic parameters were determined at 25±1°C, 70±10% RH and 12:12 (L:D). Significant differences were obtained in predation and oviposition rates between the two predators, irrespective of the prey density. Pre- and post-oviposition periods were significantly longer for N. barkeri than for P. longipes. In contrast, the oviposition period was significantly longer for P. longipes than for N. barkeri. Moreover, demographic parameters differed significantly between the two predators. Therefore, P. longipes would be a better predator for T. evansi compared to N. barkeri and could be recommended in biological control programs against this mite pest in Benin and potentially in West Africa.